2014
DOI: 10.1590/s1516-89132014000200015
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical and molluscicidal activity of Mikania glomerata Sprengel (Asteraceae) in different lifestages of Subulina octona (Mollusca, Subulinidade)

Abstract: The objective of this work was to study the molluscicidal activity of aqueous extract of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 20 publications
0
2
0
1
Order By: Relevance
“…de Souza and colleagues also used terrariums; however, they pulverized 10 mollusks for terrariums with 20 mL of extract solutions [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…de Souza and colleagues also used terrariums; however, they pulverized 10 mollusks for terrariums with 20 mL of extract solutions [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Produtos sintéticos utilizados para controle de moluscos terrestres são caros e muitas vezes causam danos ao meio ambiente e a saúde humana (Ferreira et al, 2009;Miranda et al 2011). No Brasil a maioria dos trabalhos sobre atividade moluscicida utilizando extratos vegetais está relacionada ao molusco aquático Biomphalaria glabrata (Say, 1818), existindo poucos estudos relatando a ação moluscicida de plantas sobre moluscos terrestres, sendo, contudo, necessários novos estudos (Ferreira et al, 2009;Silva et al 2012;Souza et al 2014).…”
Section: Introductionunclassified
“…The extract of M. oleifera seeds contained bioactive molecules including saponins, lectins, (Ibrahim and Abdalla, 2017) which were known by its molluscicidal activity (Augusto and de Mello-Silva, 2018). Francis et al (2002) reported that the molluscicidal activity of saponins is due to their characteristic detergent effect on epithelial tissues of the snails and that of Flavonoids may act by inhibiting the detoxification system of the snail (de Souza et al, 2014).…”
Section: Discussionmentioning
confidence: 99%